Randomness assisted imaging - Singh R.K. (My University, 2025)
Randomness in the light usually appears as a noise and obstacle in the optical imaging. Nevertheless, these random patterns can be used to design and develop new and un-conventional imaging methods. In this paper, we discuss and highlight potential of randomness assisted imaging. © 2023 JSAP-Optica Joint Symposia in Proceedings JSAP-Optica Joint Symposia 2023 Abstracts, JSAP 2023. All rights reserved.